PENGEMBANGAN MODEL PEMBATIK MELALUI MEDIA CLASSROOM DI MI MIFTAHUL HIDAYAH - Rif'atul Fadilah; Andi Prastowo; Zahratun Naemah; Zikraul Husna; Tiara Permata Bening (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to describe the development of technology-based learning models through classroom media for elementary/MI children. This study uses a qualitative approach because it aims to provide information, understanding and description of the content and quality of the content that occurs as the target or object of research. The term description is research that is intended to make a description of the events that took place. Data is collected and analyzed and abstracted, and theories will emerge that will show the results of qualitative research findings. Then the results of this journal research show that: First, the development of technology-based learning models is an effort made to develop learning that is in accordance with the demands of an increasingly modern era and full of advanced technology. Second, the use of classroom media on Google is an alternative to continue to carry out learning during this pandemic.